Some Thoughts on the Remembering (and Dismembering) of Lucretius’s De rerum natura in Translations, Commentaries, and Philosophical Poems, 1650-1750 - John Baker (XVII-XVIII)
In the story and history of the survival and reception of the works of the Greek philosopher and the Roman poet who constitute the Epicurus-Lucretius tandem across the centuries, from the fourth century BCE (Epicurus) and the first century BCE (Lucretius) up to the present time, there have been many twists and turns. This essay will review some of the ways in which Lucretius’s De rerum natura was remembered, but also misremembered and dismembered, in England in the period 1650-1750. The domain of inquiry will, in particular, concern translations, published or unpublished at the time, essentially in the latter half of the seventeenth century, and the advent of that magnum opus of eighteenth-century poetry which is the philosophical poem, looking briefly at two of the many, and diverse, philosophical poems of the period, Sir Richard Blackmore’s Creation and Alexander Pope’s An Essay on Man.